Analysis of Working Time of Bubu Catching Equipment Craftsmen (Case Study in Tellu Siattinge District, Bone Regency) - Yasmin, Yasmin; Fachry, Mardiana E.; Fakhriyyah, Sitti; Adhawati, Sri Suro; Wahid, Abd.; Mustafa, Muhammad Dalvi (PONGGAWA : Journal of Fisheries Socio-Economic, 2021)
This study aims to determine how much work time the fishing gear craftsmen work in the Tellu Siattinge District and to determine the factors that influence the working time of the trap fishing gear craftsmen in Tellu Siattinge District. This research was conducted from May to June 2021 in Tellu Siattinge District, Bone Regency. The type of research used is a quantitative approach with a survey method. The sampling technique used is proportional sampling. The data analysis of working time is carried out by calculating the amount of time spent by craftsmen and using tabulated primary data, while the factors that affect the work time use multiple linear analysis and statistical tests. From the results of the study, it was found that the working time of frame makers was 0.63 HKP/day, netting craftsmen were 0.25 HKP/day and bottom net makers were 0.34 HKP/day. The factors of wages, age, education and work experience simultaneously have a significant effect on the working time of fishing gear craftsmen in Tellu Siattinge District. Partially, the wage factor and work experience have a significant effect, while the age and education factors have no significant effect on the workload of fishing gear craftsmen in Tellu Siattinge District.